2015
DOI: 10.18074/cnuiibf.238
|View full text |Cite
|
Sign up to set email alerts
|

Liderlik, Motivasyon ve Ödüllendirme İlişkilerinin İncelenmesinde Kısmi En Küçük Kareler Yol Analizinin Kullanılması

Abstract: ÖzBu çalışmanın amacı sosyal bilimler alanında yapılan çalışmalarda sıkça kullanılan, yol analizi ve doğrulayıcı faktör analizi gibi çok değişkenli istatistiksel yöntemler arasında ortak noktayı temsil eden yapısal eşitlik modellemesine yeni bir yaklaşım olan kısmi en küçük kareler yol analizi yöntemini tanıtmak ve yöntemin kullanılabilirliğini liderlik, motivasyon ve ödüllendirme üçgeninde kavramların birbirine etkisini inceleyerek ve kavramlar arasındaki ilişkiyi ortaya çıkartarak açıklamaktır. Çalışma için … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 3 publications
0
10
0
3
Order By: Relevance
“…Thoonen, Sleegers, Oort, Peetsma and Geijsel (2011) found in their research that the motivational factors were mediating the effects of the school organizational conditions and leadership practices on the teacher learning and teaching practices. Additionally, Bulut and Çavuş (2015) found that the leadership has a statistically significant effect on the motivation and reward and the rewarding has also on the motivation. As a result of their research, it has been concluded that the factors that influence the establishment of the concept of leadership have an important place in the relation to the leader-motivation.…”
Section: The Purpose Of the Researchmentioning
confidence: 97%
See 2 more Smart Citations
“…Thoonen, Sleegers, Oort, Peetsma and Geijsel (2011) found in their research that the motivational factors were mediating the effects of the school organizational conditions and leadership practices on the teacher learning and teaching practices. Additionally, Bulut and Çavuş (2015) found that the leadership has a statistically significant effect on the motivation and reward and the rewarding has also on the motivation. As a result of their research, it has been concluded that the factors that influence the establishment of the concept of leadership have an important place in the relation to the leader-motivation.…”
Section: The Purpose Of the Researchmentioning
confidence: 97%
“…The Implications Towards the Theory Also, it has been identified in the previous researches made by Ishaq and Segoro (2015), Kanayran (2015), Thoonen et al (2011), and Bulut and Çavuş (2015) that the leadership applications have affected the employees' motivations. The teachers' motivation can be achieved through a few simple actions, such as an exchange in the leadership and management activities, as Cutlip et al (2005) have stated.…”
Section: Conclussion and Suggestionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Değişkenlere ilişkin R 2 , Q 2 ve VIF değerleri Tablo 7'de yer almaktadır. (Bulut ve Çavuş, 2015). Yeniden örnekleme metodunun uygulanmasından sonra yapısal eşitlik modeli ve t değerleri Şekil 3'teki gibi görünmektedir.…”
Section: Araştırmada Kullanılan öLçeklere İlişkin Normallik Testiunclassified
“…Motivation, a term that arises out of the lack of an individual's desire to act with energy and passion (Kim, 2006), which is relevant to the reason of a behavior or the causes of the individual behavior and which may vary due to the difference of the individual behaviors and individual needs (Ryan et al, 2011), is defined as the driving force that revitalizes and controls the behavior such as learning for a purpose, doing something or acting (Bulut and Çavuş, 2015). In another definition, motivation is defined as a psychological process for uncovering voluntary behaviors to achieve individual and organizational goals and ensuring the continuity of these behaviors (Pool and Pool, 2007).…”
Section: Motivation In Organizations and Motivation Dimensionsmentioning
confidence: 99%